Risk Factors of Prolonged QTc Interval in Patients with Drugs-Resistant Tuberculosis - Andika Pradana; Katharine Katharine; Parluhutan Siagian (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Drug-Resistant Tuberculosis (DRTB) is still one of the biggest health problems worldwide. In 2016, WHO published new guidelines for DRTB management using 7 second-line drugs that only required 9-11 months of treatment with a higher success rate. Unfortunately, one of the side effects was the possibility of a prolonged QT-c interval on electrocardiography. However, to date there have been no known factors which increased the risk of QTc prolongation in DRTB patients.Methods: This was a retrospective cohort study that analyzed the medical records of 50 DRTB patients who underwent treatment from August 2017 to August 2020 at the DRTB Clinic of Adam Malik Hospital Medan. Statistical analysis was performed using logistic regression to determine the factors which increased the risk of QTc prolongation in DRTB patients.Results: Of the 50 study samples consisting of 40 MDR TB patients, 9 pre-XDR TB patients and 1 XDR TB patient, 14 (28%) subjects were found to have QTc prolongation. There were no correlation between the regimen type (P = 0.51), age (P = 0.40), sex (P = 0.74), nutritional status (P = 0.35) and comorbid diseases (P = 0.31) on the prolongation of QTc interval. Patients receiving clofazimine had a greater percentage (78.6% vs 21.4%) to experience prolonged QTc interval, although not statistically significant (P = 0.41). Conclusion: Treatment regimen, age, sex, nutritional status and comorbid disease were not associated with prolonged QTc interval in DRTB.